MEDIA PEMBELAJARAN KEMP BERBASIS KOOPERATIF LEARNING MATA PELAJARAN AKIDAH AKHLAK - mukarromah, Jazirotu zamzam (IJIT: Indonesian Journal of Islamic Teaching, 2020)
Learning is something that is external and is deliberately designed to support the occurrence of internal learning processes within individuals to acquire competencies in the form of knowledge, skills, and attitudes needed in doing a job. This study aims to analyze the KEMP-based learning media on moral theology subjects at the Superior Private Islamic School (MIS) Nurul Islam City of Citrodiwangsan-Lumajang. As for what is applied in this study using a qualitative approach to literature. The result of this writing is that to start a good learning activity, a good instructional design is needed too, so that what is expected from learning activities can be achieved properly. moral theology learning, which is impressed as a rote-oriented and boring subject, must be changed by designing learning that involves active student participation in the learning experience. The instructional design of the Kemp model, which is collaborated with the learning strategy of the cooperative learning method, is expected to be the answer so that learning the moral theology becomes a fun learning experience and motivates students to keep learning.